MATHEMATICAL MODEL OF PARTICLE MOTION IN A VORTEX APPARATUS - Соколовська, Ірина; Крицький, Євген (SWorldJournal, 2025)
This paper presents a mathematical model of particle motion in a vortex apparatus during heat treatment. A comprehensive mathematical model has been developed, which takes into account the processes of particle heating, their three-dimensional motion, and